Transportasi Online: Analisis Bibliometrik dan Systematic Literature Review (SLR) - Dea Rizka Koesalia; Keisha Nathaya Yona Wirawan (Fakultas Teknik Universitas Cenderawasih, 2026)
Online transportation has become an essential component of modern urban mobility, significantly transforming the way people travel while creating new challenges related to service quality, safety, customer satisfaction, sustainability, and its impact on conventional public transportation. This study aims to examine the development of research on online transportation through a bibliometric analysis combined with a Systematic Literature Review (SLR). Data were collected from the Scopus database using the keyword